Implementation of ESG practices and sustainable development in the activities of second-tier banks in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2025)
Banking institutions are central to the ESG transformation of the global economy, acting as an important benchmark for assessing ESG risks. Their activities, as well as the opportunity to focus on certain sectors of the economy, make it possible to finance projects in the field of the "green" economy, which, in turn, contributes to its development. In many countries, the implementation of ESG principles through financial institutions also determines the responsibility of banks to central banks and financial regulators. This approach promotes the integration of ESG principles at all levels of the banking system, promoting them among the general public.The concept of sustainable development refers to a medium- and long-term economic strategy that allows modern generations to meet their needs without jeopardizing the opportunities of future generations. In this context, we can note that the ESG agenda, focused on environmental, social and managerial aspects of corporate activities, is becoming the main driver of the concept of sustainable development and is increasingly being applied in both the global and domestic business environment.The concept of green growth and sustainable development is being transformed into a global ideology that guides changes in national economies. The focus is shifting from quantitative performance indicators to rational choice conditions. Rationality in decision-making is becoming a key factor in achieving sustainable green growth, which may require rethinking existing financial models that support such dynamics. Thus, the most pressing issues related to sustainable growth are the transformation of financial systems and the creation of new financial paradigms based on the principles of responsible investment and corporate social responsibility. The study examines the implementation of ESG practices and the concept of sustainable development in the activities of second-tier banks in the Republic of Kazakhstan.Key words: financial market, sustainable development, ESG banking, integration of financial instruments, green financing.